Development of Science, Technology, Engineering, and Mathematics (STEM)-Based Chemistry E-module Learning Materials on the Topic of Reaction Rate - Oktariani Oktariani; Endita Rifki Saputri (University of Muhammadiyah Malang, 2024)
Teaching materials are important components in learning, so they need more attention. This study aimed to determine the validity and response of the target audience to a STEM-based chemistry e-module on reaction rate. The research used the ADDIE development model, which consists of five stages: Analyze, Design, Develop, Implement, and Evaluate. However, this research was limited to the implementation stage through trials with a small group. The research instruments used were interview guidelines, student needs questionnaire sheets, validation sheets, and teacher and student response questionnaire sheets. The subjects of this study were 3 expert lecturers, 2 expert chemistry teachers, and 30 students of class XII IPA at SMA Negeri 2 Sentajo Raya. The results showed that the STEM-based chemistry e-module on reaction rate material was feasible to use with a validity value of 89.6% (very feasible criteria). Based on the responses of the target audience, it can also be concluded that the e-module is feasible to use with a teacher response percentage of 92% and students 88%. This means that e-modules are feasible to use as teaching materials on reaction rate materials at SMAN 2 Sentajo Raya. Therefore, to apply and implement this e-module to other schools, further studies are needed.